Simulation of the global monsoon sequence by a simple ocean-atmosphere interaction model (MAUSAM, 1978)
A simple model is utilized to study the annual monsoon sequence of an atmosphere ocean system constructed to approximate the gross features of the continent-ocean distribution of the earth. The general three-dimensional structure of the system is simplified by division into a. number of domains, so chosen as to Isolate regions of similar character or similar lower boundary conditions. The governing primitive equations are averaged in longitude between the limits of each domain and neighbouring domains interact via east-west interdomain fluxes of heat and momentum. From this process, coupled sets of two-dimensional primitive equations evolve in latitude-height plane. The oceans are represented as simple adjective mixed layers In which the vertical structure is represented by two layers and advection forced by the latitudinal density variation.To accomplish the horizontal coupling of adjacent domains, a parameterization is developed based on the theory of slowly-varying or quasi-stationary modes. The character of the parameterization is such as to reduce to a quasi-geostrophic nature in mid-latitudes and to a longitude-height plane confinement at low latitudes, the latter consistent with an east-west Walker type solution. Coupling between the ocean and the atmosphere is accomplished by wind stress and lower boundary heating.Results are presented for a four-domain version of the model in which solar heating is allowed to follow an annual cycle. The effect of the vastly different time scales introduced into the model by the land and ocean regions is most marked in providing a diversity of response between hemispheres at different seasons and between land and ocean domains. The most interesting features are the rapid equinoctial transitions and the development of a strong easterly jet stream in the early northern heq1isphere summer and its rapid decay In early autumn; features which the oceanic southern hemisphere does not reproduce.